Flood hazard and vulnerability-related research in Romania. The Gordian knot of conceptual and operational overlapping (GeoPatterns, 2025)
Scientific research is of critical importance for salient decision-making aiming to reduce flood risk, but the interwoven character of risk-related terminology and the demanding task of operationalising concepts like hazard and vulnerability frequently hinder scientific advancement. This paper documents the i) meaning of the terms hazard and vulnerability, and ii) operationalisation of these concepts, in the scientific research focusing on river floods in Romania. A 4-step semi-systematic literature review was performed, setting the time frame to 2000-2022. The literature review points out the conceptual and operational overlapping of the flood hazard and vulnerability, as well as their dynamics and spatial focus. Flood hazard is operationalised mostly through hydraulic modelling and spatial analysis, while flood vulnerability is frequently assessed via index-based methodologies. There are several studies that operationalise flood vulnerability or hazard using a methodology that targets flood risk. Another tendency observed in the literature is to choose titles referring to one of the flood risk components, but to formulate aims that concern the other; in certain cases only to assess their intersection. By addressing these issues, we aim to open the way to flood hazard and/or vulnerability assessments that properly fit the terminological and methodological paradigms.